(untitled) (Journal Of Educational and Psychological Researches, 2012)
Rights of child in the community crisis Iraqi child model The study aimed to identify the types of violation against children in the Iraqi crisis as well as to develop community coping mechanisms to these violations and promote the rights of the child health psychological , social and legal . the first chapter discusses the research problem and its importance and purpose of the research problem and its importance and purpose of the research and the most important terms in the A- Rights of the child ,B- crisis , chapter 2 rights of the child ensure the historical roots , of children’s rights in the holy quran and the sunnah, and legal rights through the twentieth century and the beginnings of century xx, the se through the twentieth century and the beginnings of century xx, the section of the CRC as well as optional protocol to the convention on the rights of the child on the sale of children , child prostitution and child pornography in the united (protection and psychological and social health ) . the third chapter focused on violations of the rights of children in armed conflict and social effects of crises associated with them include an introduction and first section of child rights violations of health and them stopovers on war and its role in the violations of those rights the second section of violations of the rights of children in recruitment and involvement in armed conflict ,the third section of the armed conflict and crimes of sale and trafficking of children, the fourth section of violations of children’s rights legal introduction introductory A-children events and Iraqi legislation to child labor, while section v violation of the rights of children with social , psychological ,section vi crises community took up –the social effects of crises 6- dimensions of the crisis of community 1- in field of social welfare and child mental Iraqi 2- in the health field 3- in the legal field , the discussion touched on the most important recommendations of the research, then the conclusion, reinforced by more than forty find the source of Arab and foreign, as well as internet sources .